NILAI-NILAI PENDIDIKAN ISLAM DALAM AL-QUR’ANvSURAH AL-A’RAF AYAT 199-202 - Zulkifli Agus (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
In living their lives, Muslims have been given guidance and instructions by Allah SWT so that they can lead their lives well and remain within the framework of the Shariah as prescribed. This guidance is none other than the holy book of the Qur'an. The Qur'an is the scripture revealed by Allah to provide guidance to those who do good deeds, to bring glad tidings of salvation to the righteous, and to serve as a warning of eternal punishment for wrongdoers. It consists of pages filled with wise counsel and admonitions, leading the believers from darkness into light.